(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to identify the impact of the reciprocal teaching strategy on the achievement of the students of the second stage in the Department of Holy Qur’an Sciences and Islamic Education in the subject of modern curricula. The researcher relied on a theoretical background and previous studies to benefit from them in the research requirements and procedures.The researcher adopted the experimental approach to reach the results of the research, and the research sample consisted of (63) male and female students, with (32) for the experimental group and (31) for the control group, who were chosen randomly.The researcher prepared an achievement test of thirty questions, and after confirming the validity of the test and its stability, the data were processed using statistical methods such as: (arithmetic mean, standard deviation, binary analysis of variance,